Biofunctional Micropatterning of Thermoformed 3D Substrates. (22nd July 2013) - Waterkotte, Björn; Bally, Florence; Nikolov, Pavel M.; Waldbaur, Ansgar; Rapp, Bastian E.; Truckenmüller, Roman; Lahann, Jörg; Schmitz, Katja; Giselbrecht, Stefan
<x xml:space="preserve">Abstract</x> Mimicking the in vivo microenvironment of cells is a challenging task in engineering in vitro cell models. Surface functionalization is one of the key components providing biochemical cues to regulate the interaction between cells and their substrate. In this study, two different approaches yield biofunctional surface patterns on thermoformed polymer films. The first strategy based on maskless projection lithography enables the creation of grayscale patterns of biological ligands with a resolution of 7.5 μm in different shapes on a protein layer adsorbed on a polymer film. In the second strategy, polymer films are micropatterned with different functional groups via chemical vapor deposition polymerization. After thermoforming, both types of pattern can be decorated with proteins either by affinity binding or covalent coupling. The 3D microstructures retain the biofunctional patterns as demonstrated by selective cell adhesion and growth of L929 mouse fibroblasts. This combination of functional micropatterning and thermoforming offers new perspectives for the design of 3D cell culture platforms.